PROGRAM SUPERVISI AKADEMIK - Tamlekha Hayani (Program Studi Manajemen Pendidikan Islam, 2022)
Academic Supervision is a supervisory activity aimed at improving conditions in an effort to improve the quality of student products through efforts to motivate, foster and direct people related to academic activities. Therefore it can be concluded that academic supervision activities are very important and must be carried out continuously by school principals to educators. Because academic supervision can improve the performance of educators, which in turn can improve the quality of learning itself. The objective is to find out how the academic supervision program is. This research method is a qualitative descriptive method and is supported by accurate data and based on relevant theory. The results of this study are in the planning of academic supervision which has a very important position in the process of academic supervision. Planning for an academic supervision program is compiling a monitoring planning document for a series of activities to help teachers develop the ability to manage the learning process to achieve learning goals. The benefits of planning an academic supervision program are: a). Guidelines for implementation and academic supervision. b). To equalize the perception of all school members about the educational supervision program. c). Guarantee of savings and effectiveness in the use of school resources (energy, time and costs).